THE INFLUENCE OF TEACHER PROFESSIONALITY ON THE DEVELOPMENT OF MENTAL HEALTH AND THE ZONE OF PROXIMAL DEVELOPMENT IN CHILDREN - Sakdiyah, Holifatus; Puspitasari, Nita; Wahidah, Finadatul (International Conference on Humanity Education and Society (ICHES), 2024)
As school mentors, teachers have a role in influencing and fostering children's development. This research aims to explore teacher professionalism's influence on mental health development and the Zone of Proximal Development (ZPD) in early childhood. Teacher professionalism, which includes competence, skills, and attitudes in teaching, is crucial in creating a learning environment that supports children's holistic development. In the context of early childhood education, two critical aspects that are influenced by teacher professionalism are children's mental health and progress in children's ZPD. The approach used in the research is quantitative with a causal explanatory type. Researchers use populations and samples; this sampling technique uses proportionate stratified random sampling. Data collection in this research was a questionnaire with a Likert scale. Data analysis using WarpPLS 4 software goes through two stages of analysis, namely the inner model and the outer model. This research results in Hypothesis 1 testing teacher professionalism (X1) on mental health (Y1). The test results obtained a p value of 0.000 < 0.005, and a T Statistics value of 7,954> 1.96 so that a decision could be made: Ho was rejected, and Ha was accepted with the statement: teacher professionalism (X1) influences mental health (Y1); Hypothesis 2 tests teacher professionalism (X1) against the Zone of Proximal Development (Z1). The test results obtained a p value of 0.000 < 0.005, and a T Statistics value of 6,865> 1.96 so that a decision could be made: Ho was rejected, and Ha was accepted with a statement; Teacher professionalism (X1) influences the Zone of Proximal Development (Z1). Hypothesis 3 tests teacher professionalism (X1) on mental health (Y1) and Zone of Proximal Development (Z1) simultaneously. The test results obtained a p value of 0.000 < 0.005, and a T Statistics value of 4,819> 1.96 so that a decision could be made: Ho was rejected, and Ha was accepted with the statement: teacher professionalism (X1) influences mental health (Y1) and the Zone of Proximal Development (Z1 ) simultaneously.